Study on microstructure and mechanical properties of 4Cr5MoSiV1 steel manufactured by selective laser melting. Issue 2 (April 2021) - Bi, Yanchao; Tao, Fenghe; Jia, Changzhi; Chen, Shuai
Abstract: The 4Cr5MoSiV1 steel samples were manufactured by selective laser melting technique. The effects of laser line energy density on microstructure, microhardness and wear resistance were analyzed. The relationship between microstructure and mechanical properties was studied. The results show that when the laser line energy density is too high, the grain size of the sample is larger, and there is a small amount of granular second phase precipitates in the sample. When the laser line energy density is too low, the grain size of the sample is small, and the grain shape is irregular, and there are obvious pores. When the laser line energy density is 633Jm -1, the microstructures of the samples are uniform in size and regular in shape. The highest microhardness is 682.3HV, and the lowest wear rate is 0.425 × 10 -10 kg N -1 m -1 .